Implementasi Pembelajaran Teknologi Informasi Berbasis Video Pada Mahasiswa Semester 1 Program Studi Matematika Universitas Muhammadiyah Kotabumi - Khotimah, Khusnul; Venty Meilasari (Eksponen, 2025)
This study aims to determine the effectiveness of implementing video-based Information Technology learning on the learning outcomes of first-semester students in the Mathematics Study Program at Universitas Muhammadiyah Kotabumi. The research method used is a pre-experimental design with a one-group pretest-posttest model. The research sample consisted of 28 students. Data were obtained through pretest and posttest assessments, as well as a student perception questionnaire. The analysis results showed that the average pretest score was 56.82 with a standard deviation of 6.47, while the posttest average increased to 78.18 with a standard deviation of 6.79. The Shapiro-Wilk normality test indicated that the data were normally distributed, with significance values of 0.645 for the pretest and 0.151 for the posttest. The paired sample t-test produced a significance value of 0.000 (<0.05), indicating a significant difference between pretest and posttest scores. In addition, the analysis of student perception questionnaires showed an average score of 4.38, categorized as “strongly agree.” Thus, video-based Information Technology learning is effective in improving learning outcomes and receives a positive response from students.